2015
DOI: 10.3233/bme-151434
|View full text |Cite
|
Sign up to set email alerts
|

Fully automatic scheme for measuring liver volume in 3D MR images

Abstract: Abstract. In this paper, a fully automatic scheme for measuring liver volume in 3D MR images was developed. The proposed MRI liver volumetry scheme consisted of four main stages. First, the preprocessing stage was applied to T1-weighted MR images of the liver in the portal-venous phase to reduce noise. The histogram of the 3D image was determined, and the second-to-last peak of the histogram was calculated using a neural network. Thresholds, which are determined based upon the second-to-last peak, were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…A 3D liver model guided by a precomputed probability map was used by Bereciartua et al [4], which achieved a mean Dice of 0.90 for patients with healthy livers. Le et al used a histogram-based liver segmentation with a subsequent geodesic active contour refinement step and reported a mean Dice of 0.91 [5]. Huyhn et al proposed a method based on watershed transformation and active contours, which achieved a mean Dice of 0.91 [6].…”
Section: Introductionmentioning
confidence: 99%
“…A 3D liver model guided by a precomputed probability map was used by Bereciartua et al [4], which achieved a mean Dice of 0.90 for patients with healthy livers. Le et al used a histogram-based liver segmentation with a subsequent geodesic active contour refinement step and reported a mean Dice of 0.91 [5]. Huyhn et al proposed a method based on watershed transformation and active contours, which achieved a mean Dice of 0.91 [6].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the volume of the liver may be measured with automatic volume measurement methods in recent studies [37][38][39] . In these methods, the measurements may be made by using various measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Prior to the use of deep learning (DL), segmentation would most frequently be based multi-atlas approaches. [1] uses 3D models of the liver and probability maps, [2] is based on histograms to segment the liver, followed by active contours for refinement, [3] applies watershed together with active contours. Then deep learning-based segmentation revolutionized the field.…”
Section: Related Workmentioning
confidence: 99%